Using Board Games as Anti-Corruption and Integrity Learning Media - Sandri Justiana; Roto Priyono; Eko Nugroho (Bina Nusantara University, 2017)
One of the corruption eradication mandates assigned to the Corruption Eradication Commission (KPK) is to carry out anti-corruption education at each level of education, carry out anti-corruption public campaigns, and promote corruption eradication programmes (Law No 30/2001 on the Corruption Eradication Commission). To make anti-corruption education more effective, alternative media need to be developed that are more interesting and fun but do not detract from the essence and objectives of the learning itself. The KPK developed eight more anti-corruption and integrity board games for a wider audience, including young children, young people, students, educators, business people, and politicians. Board games are an interactive anti-corruption learning media that offer a unique way of looking at something, promote open communication, and challenge the players to work together to achieve results. Board games can be used an alternative learning media to instil anti- corruption values from a young age, and as a media for public anti-corruption promotion and campaignÂ